Metal air filter
The metal air filter with nanobranched structure was manufactured by electrodeposition method, and combined with hydrogen heat treatment and hydrochloric acid cleaning technology, the problem of high cost and low efficiency in large-area manufacturing was solved, achieving high efficiency and low cost air filtration effect.
Patent Information
- Application Number
- CN202180005554.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-09-06
- Filing Date
- 2021-10-05
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2041-10-05
AI Technical Summary
The existing HEPA air filters have high production costs and production limitations when manufacturing large-area air filters. The nanofibers produced by the traditional meltblown method are large in diameter, making it difficult to achieve low-cost and efficient filtration effects.
The metal air filter is manufactured by electrodeposition method, and nano-branched structures are formed by electrodeposition of the electrolyte in the electrolyte cell. Combined with hydrogen heat treatment and hydrochloric acid cleaning process, a filter with high-efficiency filtration performance is formed.
The manufacturing of low-cost, large-area HEPA air filters is realized, which improves the filtering efficiency and mechanical properties of the filters, reduces production costs, and achieves efficient particle capture at low energy consumption.
Smart Images

Figure CN114630714B_ABST
Abstract
Description
Technical Field
[0001] Various embodiments relate to a metal air filter and a method of making the same. Background Art
[0002] The demand for air filters has increased significantly in recent years due to increased awareness of fine dust.
[0003] An air filter is a filter medium that filters fine particles suspended in the air, and the shape and desired characteristics of the product may vary depending on the place of use and purpose.
[0004] Industrial air filters are filters used to filter fine particles from the air as it is drawn into factories and buildings from outside. Home air filters are filters used to remove fine particles from certain indoor spaces, and from the air exhausted when using large appliances such as air conditioners and vacuum cleaners.
[0005] The filter system can be composed of four stages, including a pre-filter, a functional filter, a deodorizing filter, and a high-efficiency particulate air (HEPA) filter. The pre-filter is mainly used to remove large dust and can be constructed by forming a mesh using metal or the like. About 50% of pollutants can be controlled by the pre-filter.
[0006] Functional filters are used to provide additional antimicrobial properties to the filter system and can be constructed using non-woven fabrics, etc.
[0007] The deodorizing filter is used to remove odors, and activated carbon is used as a material of the deodorizing filter.
[0008] A HEPA filter is a high-performance filter that can filter 99.97% of fine dust as small as 0.3 microns. Generally, filters that filter 95% or more of fine dust can be considered HEPA filters. HEPA filters can be formed using nanofibers.
[0009] At present, commercial HEPA filters are mainly manufactured using the melt blown method. According to the melt blown method, the thermoplastic resin is melted and extruded and discharged through a nozzle, and high-temperature and high-pressure air is applied to the molten polymer. Subsequently, the polymer is stacked on a conveyor belt in an extremely fine state and combined together by the self-adhesive effect generated by the waste heat, and then manufactured into a nanofiber structure. The diameter of the nanofiber structure produced by the melt blown method is about 0.8μm to 1μm, and particles such as fine dust are captured by van der Waals forces.
[0010] Recent studies have shown that electrospinning can be used to melt thermoplastic resins instead of meltblowing. When using electrospinning to melt thermoplastic resins, the diameter of the nanofiber structure can be reduced to about 0.3 μm compared to conventional meltblowing, and high efficiency can be obtained with limited pressure loss through air filters used in clean rooms of semiconductors or operating rooms. However, this method has production cost issues and limitations in the process of manufacturing large-area air filters.
[0011] (Non-patent document 1)
[0012] 1. Kadam, Vinod & Wang, Lijing & Padhye, Rajiv., “Electrospun nanofibrematerials to filter air pollutants-A review,” Journal of Industrial Textiles, 2016, 47.10.1177 / 1528083716676812. Summary of the invention
[0013] Technical issues
[0014] An object of various embodiments of the present disclosure is to provide a method for manufacturing a HEPA filter that has lower cost than conventional methods and enables large-area process.
[0015] The purpose of various embodiments of the present disclosure is to provide a method for manufacturing a low-cost and large-area HEPA filter using electrodeposition using metal as a raw material.
[0016] It is an object of various embodiments of the present disclosure to provide a thermal and / or chemical treatment method for manufacturing a filter having a micro-network structure with nano-branches using electrodeposition and improving the performance of the manufactured filter.
[0017] The technical problems to be overcome in the present disclosure are not limited to the above-mentioned technical problems. A person skilled in the art can clearly understand other unmentioned technical problems from the following description.
[0018] Solution
[0019] One embodiment is a metal air filter comprising: a filter formed of a metal material by electrodeposition and having a nano-branched structure; an ion generator that transfers negative charges to particles to be captured by the filter; and a power source that provides a positive voltage to transfer positive charges to the filter and provides a negative voltage to the ion generator.
[0020] The filter is formed by electrodeposition of an electrolyte in an electrolytic cell including a metal mesh attached to a cathode, a metal plate attached to an anode, and an aqueous solution. The filter has a nano-branched structure.
[0021] The filter is formed by additionally performing a hydrochloric acid cleaning process.
[0022] The aqueous solution contained a halogen element, and a voltage of 0.7V was applied between the cathode and the anode.
[0023] The aqueous solution contained copper sulfate and sulfuric acid, and the voltage applied between the cathode and the anode was 2.4V.
[0024] Only one of the two surfaces of the metal plate in the electrolytic cell is opened, so that only the open surface of the two surfaces of the metal plate participates in the electrochemical reaction of the electrodeposition. The distance between the metal mesh and the metal plate in the electrolytic cell is set to 5 mm.
[0025] The filter formed by the electrodeposition is additionally subjected to a mechanical compression process to obtain the filter.
[0026] The filter formed by the electrodeposition is additionally subjected to a heat treatment using hydrogen gas to form the filter.
[0027] The heat treatment using hydrogen is performed by the steps of: placing a graphite plate in a vacuum tube, placing the filter formed by the electrodeposition on the graphite plate; injecting a mixed gas containing hydrogen into the vacuum tube; and applying heat to the vacuum tube.
[0028] Another embodiment is a method for manufacturing a metal filter, which includes: connecting a metal mesh with a metal wire wound in the metal mesh to a cathode of an electrolytic cell; connecting a metal plate to an anode of the electrolytic cell; adding an aqueous solution so that the metal mesh and the metal plate of the electrolytic cell are immersed; and forming the filter by applying a voltage between the cathode and the anode of the electrolytic cell to perform electrolysis.
[0029] The aqueous solution contained a halogen element, and a voltage of 0.7V was applied between the cathode and the anode.
[0030] The aqueous solution contained copper sulfate and sulfuric acid, and the voltage applied between the cathode and the anode was 2.4V.
[0031] Forming the filter further includes: connecting the nano branches in the filter obtained by the electrolysis to each other and performing a heat treatment using hydrogen to reduce the diameters of the nano branches.
[0032] Forming the filter further includes: performing a hydrochloric acid cleaning process to remove halogen elements contained in the filter obtained by the electrolysis.
[0033] Forming the filter further includes: performing a mechanical compression process on the filter obtained by the electrolysis.
[0034] Only one of the two surfaces of the metal plate in the electrolytic cell was opened, and the distance between the metal mesh and the metal plate in the electrolytic cell was set to 5 mm.
[0035] Still another embodiment is a filter for filtering particles contained in air, the filter being formed of a metal material through electrodeposition and having a nano-branched structure.
[0036] The nano-branched structure is formed by the guidance of the halogen element contained in the aqueous solution provided in the electrolytic bath of the electrodeposition.
[0037] The nano-branches of the filter are connected to each other through a hydrogen-based heat treatment.
[0038] The halogen elements used to form the filter are removed through a hydrochloric acid cleaning process.
[0039] The filter is formed by the electrodeposition and subsequent mechanical compression.
[0040] Beneficial Effects
[0041] The method proposed in the present disclosure can manufacture the filter in a simpler and lower-cost manner than the traditional process.
[0042] The filter manufacturing method based on electrodeposition proposed in the present disclosure is capable of manufacturing metal wires with various sizes and large-area filters.
[0043] The filter manufactured according to the method proposed in the present disclosure captures particles by using Coulomb force which is much larger than the conventional Stedward force, thereby improving the efficiency of the filter even at low energy consumption.
[0044] The method proposed in the present disclosure can improve mechanical properties and provide stability through additional heat treatment and HCl removal.
[0045] The beneficial effects that can be obtained from the present disclosure are not limited to the above-mentioned effects. Further, those skilled in the art to which the present disclosure belongs can clearly understand other unmentioned effects according to the following description. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 The concept of forming a filter by electrodeposition according to various embodiments of the present disclosure is shown;
[0047] Figure 2 An example of forming metal nano-branches in the metal mesh 130 is shown;
[0048] Figure 3 Filters formed under various conditions are shown;
[0049] Figure 4 shows the size of the electrodeposition area as a function of the voltage applied during electrolysis;
[0050] Figure 5 shows the size of the electrodeposition area according to the diameter of the metal wire and the distance between the metal wires used to form the metal mesh 130, the metal mesh 130 being wound by the metal wires;
[0051] Figure 6 illustrates a filtering mechanism according to various embodiments;
[0052] Figure 7 The present invention shows a test device for testing the performance of the filter manufactured by electrodeposition proposed in the present invention;
[0053] Figure 8 shows the particle concentration after filtration measured by a particle counter as a function of various voltages applied to the filter;
[0054] Fig. 9 The shape of the filter after filtration is shown;
[0055] Fig.10 The nano-branched structure of the filter before and after heat treatment is shown;
[0056] Fig.11 The performance of the filter before and after heat treatment is shown;
[0057] Fig.12 shows the structure of the filter before and after cleaning with hydrochloric acid;
[0058] Fig.13 The performance of the filter before and after washing with hydrochloric acid is shown;
[0059] Fig.14 The performance of the filter to which both heat treatment and hydrochloric acid cleaning were applied is shown;
[0060] Fig.15 A flow chart showing a process for making a filter using electrodeposition according to various embodiments;
[0061] Fig.16 Filters formed by different applied voltages are shown;
[0062] Fig.17 Filters formed during different electrodeposition time intervals are shown;
[0063] Fig.18 The structure of the filter formed by electrodeposition using an aqueous solution containing no halogen elements is shown;
[0064] Fig.19 The performance of the filter produced without halogen elements in the aqueous solution is shown;
[0065] Fig. 20 A simulation environment is shown;
[0066] Fig.21A , Fig. 21B , Fig. 21C and Fig.21D shows a simulation graph when the counter electrode participates in an electrochemical reaction;
[0067] Fig.22A , Fig. 22B and Fig. 22C A simulation curve diagram showing changes in the distance between electrodes when a single surface of the counter electrode participates in an electrochemical reaction;
[0068] Fig.23 The concept of mechanically compressing a filter formed by electrodeposition is shown;
[0069] Fig.24 The filter is shown before and after compression;
[0070] Fig.25 is a graph showing filter thickness as a function of pressure applied during mechanical compression;
[0071] Fig.26 shows the filter thickness as a function of the pressure applied during mechanical compression;
[0072] Fig. 27 The results of the pilling off test of the filter are shown;
[0073] Fig.28 The factors affecting the pressure difference in the filter are shown;
[0074] Fig.29 It is a structural diagram of heat treatment of the filter using hydrogen;
[0075] Fig.30 is a graph showing the average diameter of the wire as a function of temperature during heat treatment of the filter;
[0076] Fig.31 The filter proposed in the present disclosure is shown to be heat treated using conventional argon and hydrogen;
[0077] Fig.32 The pilling test results of the filter are shown;
[0078] Fig.33 A used filter and a cleaned filter are shown;
[0079] Fig.34 is a graph showing the change in differential pressure due to cleaning.
[0080] When describing the drawings, the same or similar components may be marked with the same or similar reference numerals. DETAILED DESCRIPTION
[0081] The embodiments disclosed in this specification will be described in detail below in conjunction with the accompanying drawings. Regardless of the figure number, the same or similar elements will be represented by the same figure number, and repeated description thereof will be omitted.
[0082] In addition, in the following description of the embodiments disclosed in this specification, in order to avoid making the subject matter of the embodiments disclosed in this specification unclear, the detailed description of the known technologies mentioned herein is omitted. In addition, the drawings are only used to more easily describe the embodiments disclosed in this specification. The technical spirit disclosed in this specification is not limited by the drawings. Any modifications, equivalents and substitutions made within the spirit and scope of the present invention should be understood to be included in the drawings.
[0083] Although terms including ordinal numbers such as first and second, etc. may be used to describe a plurality of components, the plurality of components are not limited by the above terms. These terms are only used to distinguish one component from other components.
[0084] When it is mentioned that a component is "connected" or "coupled" to another component, the component may be directly connected or coupled to the other component, but it should be understood that another component may exist between them. On the other hand, when it is mentioned that a component is "directly connected" or "directly coupled" to another component, it should be understood that no other components may exist between them.
[0085] [First embodiment]
[0086] Figure 1 The concept of forming a filter by electrodeposition according to various embodiments of the present disclosure is shown.
[0087] Electrodeposition means that the electrolyte is released by electrolysis and adsorbed on the electrode surface.
[0088] refer to Figure 1 , discloses an electrolysis device 100, which includes an electrolytic cell 110 and a power source 120 for electrodeposition. The electrolytic cell 110 has a cathode and an anode, the cathode is connected to the negative (-) terminal of the power source 120, and the anode is connected to the positive (+) terminal of the power source 120. A metal mesh 130 formed by winding a metal wire is connected to the cathode connected to the negative (-) terminal of the power source 120, and a metal plate 140 is connected to the electrode connected to the positive (+) terminal of the power source 120. The metal mesh 130 and the metal plate 140 can be immersed in an aqueous solution 150. According to an embodiment, the metal mesh 130 and the metal plate 140 can be formed using a copper material, and the same result can be obtained using other metal materials besides copper.
[0089] According to one embodiment, the aqueous solution 150 may be a halogen aqueous solution. For example, copper bromide (CuBr2) may be dissolved in the aqueous solution, and thus the aqueous solution may contain halogen element bromide ions.
[0090] When the power source 120 applies a voltage, the metal in the metal plate 140 is decomposed by electrolysis and escapes into the aqueous solution 150. The metal in the aqueous solution 150 adheres to the surface of the metal mesh 130 and may thereby form metal nano-branches.
[0091] Figure 2 An example of metal nano-branches formed in the metal mesh 130 is shown.
[0092] refer to Figure 2 , the halogen ions 151 dissolved in the aqueous solution 150 can be adsorbed onto the metal wire 131 of the metal mesh 130. At this time, the halogen ions 151 are not adsorbed onto the metal wire 131 in any direction, but are adsorbed in three predetermined directions at an angle of 60 degrees to each other due to the characteristics, as shown in (e). Therefore, the halogen ions 151 can be adsorbed onto the metal wire 131 as shown in (b). In addition, the metal elements present in the aqueous solution 150 can be adsorbed onto the halogen ions 151. Therefore, as shown in (c), the metal is adsorbed onto the halogen ions 151 and grows along three specific directions, and then forms a branch shape. In addition, referring to (c), the halogen ions 151 are again adsorbed onto the metal grown in three directions in a branch shape, and the metal in the aqueous solution 150 is repeatedly adsorbed onto the halogen ions 151. Thus, the metal nano branch shape shown in (d) can be obtained.
[0093] Figure 3 Filters formed under various conditions are shown.
[0094] refer to Figure 3, enlarged views of a unit length of 500 μm are shown in (a), (b) and (c), and further enlarged views of a unit length of 2 μm are shown in (d), (e) and (f).
[0095] In addition, (a) and (d) show filters formed by conventional methods without using electrodeposition, (b) and (e) show filters formed by using electrodeposition when the aqueous solution does not contain halogen ions, and (c) and (f) show filters formed by using electrodeposition when the aqueous solution contains halogen ions.
[0096] For the electrodeposition, a voltage of 0.7 V was applied to a 0.2 molar sulfuric acid (H2SO4) aqueous solution to conduct electrolysis for 1,000 seconds. In the case of (c) and (f), 0.05 molar CuBr2 was added to the sulfuric acid aqueous solution.
[0097] refer to Figure 3 As can be seen from (a), (b) and (c), the filter formed by the electro-deposition of the aqueous solution containing halogen ions proposed in the present disclosure has a denser filter membrane. In addition, it can be seen from (d), (e) and (f) that only when the aqueous solution containing halogen ions is electro-deposited as proposed in the present disclosure can a filter membrane with a fine branch shape be formed. When the filter membrane has a fine branch shape, its contact area with the particles passing through the filter is larger, increasing the possibility of capturing particles.
[0098] Figure 4 The size of the electrodeposition area is shown as a function of the voltage applied during electrolysis.
[0099] refer to Figure 4 , when the voltage applied during the electrolysis of the electrodeposition is 0.5 V, it takes 1,500 seconds or more to complete the electrodeposition, as shown in curve 410. Meanwhile, when the voltage applied during the electrolysis is 1.5 V, as shown in curve 430, at a specific time point (e.g., Figure 4 After S1 in , the electrodeposition no longer continues but weakens due to defects caused by low mechanical properties.
[0100] When the voltage applied during electrolysis is set to 0.7 V, it can be seen that electrodeposition is completed in a reasonable time, as shown in curve 420. Therefore, applying a voltage of about 0.7 V during electrolysis to form a filter containing a nano-branched structure may be most appropriate.
[0101] Figure 5 It is shown that the size of the electrodeposition area varies according to the diameter of the metal wire and the distance between the metal wires used to form the metal mesh 130, which is formed by winding the metal wires.
[0102] Figure 5 The curve in shows the electrodeposition results when the size of the metal wires and the distance between the metal wires are as shown in Table 1 below.
[0103] [Table 1]
[0104] Curve No. Wire diameter(mm) Distance between metal wires (mm) 510 0.15 0.273 520 0.1 0.154 530 0.065 0.104
[0105] As can be seen from Table 1, the larger the curve number, the smaller the diameter of the metal wire and the smaller the distance between the metal wires. Therefore, as the curve number increases, the metal mesh 130 can be formed more densely. Therefore, when the same voltage is applied to carry out electrodeposition, it can be found that the electrodeposition is completed faster in the metal mesh 130 where the metal wires are more densely wound. However, with reference to curve 510 and curve 520, it can be understood that even if its metal wires are not more densely wound than curve 530, after a certain period of time, the electrodeposition is also completed. Therefore, it can be seen that when forming the metal mesh 130 as the basic framework of the filter, there is no particular restriction on the diameter of the metal wire and the distance between the metal wires, and it can be seen that the filter can be formed by the electrodeposition performed using metal wires of various diameters.
[0106] Figure 6 Filtering mechanisms according to various embodiments are shown.
[0107] refer to Figure 6 , the particles 610 can be anionized by the ion generator 620 before entering the filter. Similarly, the fine branches of the filter 630 are cationized by the power supply 640 providing a positive (+) voltage, and the anionized particles are adsorbed to the cationic branches of the filter by electrostatic force. In addition, only air without particles can pass through. The filter proposed in the present disclosure uses electrostatic force for particle adsorption, thereby providing a much higher removal efficiency and low pressure loss than conventional filters using van der Waals forces.
[0108] Figure 7 A test device for testing the performance of the filter manufactured by electrodeposition proposed in the present disclosure is shown.
[0109] refer to Figure 7 , the test device 700 includes a test tube 730, in which a trumpet-shaped tube is connected to a central cylinder in two directions. A filter 710 for testing is arranged in the central cylinder. A particle generator 720 for generating particles is arranged at one end of the test device in one direction. An ion generator 740 is arranged in the middle of a tube extending from the particle generator 720 to the filter 710. A particle counter 750 capable of measuring the concentration of particles entering therein through the filter 710 may be arranged in an opposite tube in which the particles continue to move after passing through the filter 710.
[0110] The efficiency of the filter 710 can be calculated as the ratio of the particle concentration after passing through the filter 710 (i.e., the particle concentration in the right chamber) to the particle concentration generated by the particle generator 720 (i.e., the particle concentration in the left chamber). The efficiency of the filter can be calculated as a percentage according to the following mathematical formula 1.
[0111] [Mathematical formula 1]
[0112]
[0113] Figure 8 The post-filtration particle concentration measured by a particle counter is shown as a function of various voltages applied to the filter.
[0114] exist Figure 8 In the figure, curve 810 shows the result of the filter using the conventional method, and curves 820 to 860 show the result when the filter including nano-branches manufactured by electrodeposition proposed in the present disclosure is used. Each curve shows the result when the voltage applied to the filter is 0V (820), 2.5V (830), 5V (840), 7.5V (850) and 10V (860), respectively.
[0115] refer to Figure 8 It can be seen that, compared with the traditional method, the filter containing nano-branches manufactured by electrodeposition proposed in the present disclosure can filter more particles, thereby significantly improving the particle removal efficiency.
[0116] refer to Figure 8 It can also be seen that the higher the voltage applied to the filter 710, the higher the filtering efficiency. For example, it can be confirmed by experiments that when 0V voltage is applied to the filter 710, 98.5% of the particles are removed; when 2.5V voltage is applied to the filter 710, 99.4% of the particles are removed; when 10V voltage is applied to the filter 710, 99.9% of the particles are removed.
[0117] Fig. 9 The shape of the filter after filtration is shown.
[0118] exist Fig. 9 In (a), the case where no voltage is applied to the filter 710 is shown, and the case where a voltage of 10 V is applied to the filter 710. In each figure, the upper figure is an enlarged view of the filter shape when the unit length is 100 μm, and the lower figure is a further enlarged view of the filter shape when the unit length is 5 μm. When the unit length is 5 μm, the nano-branched structure can be clearly seen in the enlarged view of the filter shape.
[0119] refer to Fig. 9 It can be seen that more particles are adsorbed when a voltage of 10 V is applied (b) compared to when no voltage is applied (a).
[0120] Can be used in conjunction with Figure 1 The resulting filter after electrodeposition is shown to undergo additional processing to enhance filter performance or remove hazardous substances.
[0121] According to various embodiments, heat treatment may be additionally performed on the filter formed by electrodeposition. Through the heat treatment, the nano branches are more firmly connected to the surrounding branches, thereby improving the mechanical properties.
[0122] Fig.10 The nano-branched structure of the filter before and after heat treatment is shown.
[0123] exist Fig.10 In the figure, (a) shows the nano-branched structure of the filter before heat treatment, and (b) shows the nano-branched structure of the filter after heat treatment.
[0124] refer to Fig.10 It can be seen that the nano-branch structure of the filter can be more clearly seen before the heat treatment, while after the heat treatment, the nano-branches of the filter are connected to the surrounding nano-branches. The interconnection of the filter nano-branches can improve the performance of the filter by eliminating the phenomenon of current concentration in specific branches.
[0125] Fig.11 The performance of the filter before and after heat treatment is shown.
[0126] refer to Fig.11 It can be seen that the concentration of particles passing through the filter before heat treatment 1110 is greater than the concentration of particles passing through the filter after heat treatment 1120. This indicates that the efficiency of the filter is improved after heat treatment.
[0127] According to various embodiments, the filter formed by electrodeposition can be cleaned with hydrochloric acid (HCl). The hydrochloric acid cleaning is used because it can remove potentially harmful bromine remaining in the filter.
[0128] Fig.12 The structure of the filter before and after washing with hydrochloric acid is shown.
[0129] exist Fig.12 In the figure, the structure of the filter before washing with hydrochloric acid is shown in (a), and the structure of the filter after washing with hydrochloric acid is shown in (b).
[0130] refer to Fig.12 , the filter branches after washing with hydrochloric acid are thinner than the filter branches before washing (see reference numeral 1210), and defects 1220, such as holes, may appear in some areas. This may reduce the efficiency of the filter. However, due to the hydrochloric acid washing, the proportion of bromine in the filter is reduced from 7% to 3%, thereby reducing the harmfulness of the filter.
[0131] Fig.13 The performance of the filter before and after washing with hydrochloric acid is shown.
[0132] refer to Fig.13 It can be seen that the concentration of particles passing through the filter that was not washed with hydrochloric acid 1310 is less than the concentration of particles passing through the filter that was washed with hydrochloric acid 1320. This indicates that washing with hydrochloric acid reduces the efficiency of the filter.
[0133] According to another embodiment, both heat treatment and hydrochloric acid cleaning may be applied to the filter.
[0134] Fig.14 The performance of filters to which both heat treatment and hydrochloric acid cleaning were applied is shown.
[0135] refer to Fig.14 , the concentration 1440 of particles that passed through the filter to which both heat treatment and hydrochloric acid cleaning were applied was almost the same as the concentration 1410 of particles that passed through the filter to which neither heat treatment nor hydrochloric acid cleaning was applied. Therefore, by applying heat treatment and hydrochloric acid cleaning, the filter can remove harmful bromine, enhance mechanical properties, and continue to maintain high filtration efficiency. Curve 1420 may represent the concentration of particles that passed through the filter to which hydrochloric acid cleaning was applied, and curve 1430 may represent the concentration of particles that passed through the filter to which only heat treatment was applied.
[0136] Fig.15 A flow chart is shown of a process for making a filter using electrodeposition according to various embodiments.
[0137] refer to Fig.15 In step S100, the filter manufacturing apparatus including the electrolytic cell may connect a metal mesh wound with a metal wire to a cathode connected to a negative (-) terminal of a power source, and may connect a metal plate to an anode connected to a positive (+) terminal of a power source. Here, the metal wire and the metal plate may be formed of the same metal material (e.g., copper).
[0138] In step S200, an aqueous solution containing halogen ions may be added to the electrolytic cell. At this time, the aqueous solution may be added to submerge the metal mesh and the metal plate. According to this embodiment, the halogen ions may be included in the aqueous solution by dissolving copper bromide (CuBr2) in a sulfuric acid (H2SO4) aqueous solution. In addition, other halogen ions may also be included in the aqueous solution.
[0139] In step S300, electrolysis can be performed by applying power to the cathode and the anode using a power supply. The metal elements separated from the metal plate by electrolysis are adsorbed on the metal mesh, thereby forming a filter. Here, when the metal elements are adsorbed on the metal wires of the metal mesh, the halogen ions contained in the aqueous solution can guide the metal elements to be adsorbed in the form of branches.
[0140] In addition, in step S400, heat treatment and / or hydrochloric acid cleaning may be performed on the filter formed in step S300.
[0141] The heat treatment connects the nano-branches constituting the filter to each other. Therefore, during the filtering operation, the current applied to the filter can be prevented from being concentrated on a specific branch, but evenly distributed throughout the nano-branches, thereby improving the efficiency of the filter.
[0142] The hydrochloric acid cleaning process can remove harmful halogen elements contained in the filter. However, the hydrochloric acid cleaning process makes the nano-branches of the filter thinner and may cause holes to appear in some areas, which may reduce the efficiency of the filter.
[0143] When heat treatment and hydrochloric acid cleaning are performed, a filter having similar properties to the filter formed in step S300 can be formed. Therefore, in the case of heat treatment and hydrochloric acid cleaning, harmful halogen elements can be removed and the mechanical properties of the filter can be improved while maintaining similar properties to the filter formed in step S300.
[0144] [Second embodiment]
[0145] The first embodiment described above proposes a filter and a method for manufacturing the same, and since the aqueous solution used in the electrolytic cell contains a halogen element, the filter has a branched nano-branched structure.
[0146] The second embodiment proposed in the present disclosure is to manufacture the filter by an electrodeposition method with voltage applied without adding additives to the aqueous solution in the electrolytic cell. According to this embodiment, the aqueous solution in the electrolytic cell does not contain additives such as halogen elements, but may contain 0.05 mol of copper sulfate and 0.2 mol of sulfuric acid.
[0147] In the second embodiment, in order to maximize the anisotropic growth of nano branches without additives such as halogen elements, the voltage used can be higher than the voltage used in the first embodiment. Generally, copper (Cu) has a face-centered cubic (FCC) crystal structure and has the characteristic of strongly generating current on the surface group of the most open surface when voltage is applied. Therefore, the higher the voltage applied during electrodeposition, the stronger the current generated on the surface group, so that the anisotropic growth of nano branches can be maximized. For example, when a voltage of 0.7V is applied to the electrolytic cell in the first embodiment, a voltage of 2.4V is applied to the electrolytic cell in the second embodiment. Therefore, the anisotropic growth of nano branches can be maximized. It is proposed that the aqueous solution used in the electrolytic cell contains 0.05 moles of copper sulfate and 0.2 moles of sulfuric acid without halogen elements, and the filter is manufactured by electrodeposition.
[0148] Fig.16 Filters formed by different applied voltages are shown. Fig.16 The results are shown in which a filter was formed by changing the applied voltage without adding an additive to the aqueous solution in the electrolytic cell.
[0149] exist Fig.16 Magnified views of 500 μm and 5 μm unit lengths are shown in (a), (b) and (c). The filter formed when a voltage of 1.2 V is applied during electrodeposition is shown in (a). The filter formed when a voltage of 2.4 V is applied during electrodeposition is shown in (b). The filter formed when a voltage of 4.8 V is applied during electrodeposition is shown in (c).
[0150] refer to Fig.16 It can be seen that when the uniformity of the filter gradually decreases as the applied voltage increases, the diameter of the metal wire (or nano-branch) gradually decreases. For example, the diameter of the metal wire in the filter shown in (a) is 3.1 μm, the diameter of the metal wire in the filter shown in (b) is 2.56 μm, and the diameter of the metal wire in the filter shown in (c) is 1.78 μm. Generally, the smaller the diameter of the metal wire in the filter, the higher the filtering performance. Moreover, it is important that the nano-branch grows uniformly throughout the entire area of the filter. Therefore, in a second embodiment of the present disclosure, a maximum voltage (i.e., 2.4V capable of maintaining the uniformity of the filter) can be used as an applied voltage.
[0151] Fig.17 Filters formed during different electrodeposition time intervals are shown. Fig.17 The results of forming a filter by changing the electrodeposition time without adding an additive to the aqueous solution in the electrolytic bath are shown.
[0152] exist Fig.17 (a), (b) and (c) show enlarged views of a unit length of 500 μm. The filter formed by applying voltage to the electrolytic cell for 120 seconds is shown in (a). The filter formed by applying voltage to the electrolytic cell for 300 seconds is shown in (b). The filter formed by applying voltage to the electrolytic cell for 900 seconds is shown in (c).
[0153] refer to Fig.17It can be seen that although the uniformity of the filter is improved as the electrodeposition time increases, the thickness of the filter gradually increases. For example, the filter shown in (a) has a thickness of 445 μm, the filter shown in (b) has a thickness of 464 μm, and the filter shown in (c) has a thickness of 585 μm. Generally, the smaller the thickness of the filter, the higher the efficiency. In addition, it is important that the nano branches grow uniformly in the entire area of the filter. Therefore, in a second embodiment of the present disclosure, the time for electrodeposition can be controlled to be the shortest (e.g., 300 seconds) to maintain the uniformity of the filter. The filter manufactured in the case where the aqueous solution contains halogen elements and the filter manufactured in the case where the aqueous solution does not contain halogen elements may have the differences shown in the following Table 2.
[0154] [Table 2]
[0155]
[0156] Referring to Table 2, as in the first embodiment, the filter manufactured by electrodeposition containing a halogen element in an aqueous solution has a high efficiency due to the fine nano-branch having a high specific surface area and a small pore size, but also has a high pressure loss. In addition, the filter has a mechanical property that the branches are very fine and easily broken.
[0157] On the other hand, since the filter manufactured using the halogen-free aqueous solution has relatively thick branches and a large pore size, the filter has relatively low efficiency and relatively low pressure loss. In addition, since it has relatively thick branches, the filter can have good durability. In addition, since no harmful halogen elements are used, the stability is improved. At the same time, by increasing the voltage applied to the filter to about 20V, the efficiency of the filter can be improved to a level similar to the efficiency of the filter prepared by the method according to the first embodiment. In addition, the manufacturing method according to the second embodiment may not require additional manufacturing processes, such as heat treatment and / or hydrochloric acid cleaning processes.
[0158] However, in the case of the second embodiment, only in the case of applying a voltage of 2.4 V during electrolysis and maintaining electrolysis for 300 seconds or more, the electrodeposition filled even the inside of the metal mesh, thereby obtaining a usable filter.
[0159] Fig.18 The structure of a filter formed by electrodeposition using an aqueous solution containing no halogen elements is shown.
[0160] Fig.18 The structure of the filter formed on the metal mesh 130 when a voltage of 2.4 V is applied between the negative terminal and the positive terminal of electrolysis and electrodeposition is performed for 2,880 seconds is shown.
[0161] refer to Fig.18 , because there are no halogen ions that determine the growth direction of the material to be electrodeposited, the structure of the filter formed according to the second embodiment does not have a branched shape, unlike the structure of the filter formed according to the first embodiment. However, it can be understood that the electrodeposition can be filled even inside the metal mesh 130, and a usable filter can be obtained.
[0162] Fig.19 The performance of the filter produced without halogen elements in the aqueous solution is shown.
[0163] Fig.19 The performance of a filter manufactured by electrodeposition in which a halogen element is contained in an aqueous solution and a voltage of 5 V (1920) and a voltage of 10 V (1940) are applied is shown. The performance of a filter manufactured by electrodeposition in which a halogen element is not contained in an aqueous solution and a voltage of 10 V (1910) and a voltage of 20 V (1930) are also shown.
[0164] refer to Fig.19 It can be seen that the performance of the filter manufactured when the aqueous solution contains halogen elements and a voltage of 10V (1940) is used in the process of manufacturing the filter by electrodeposition is almost the same as the performance of the filter manufactured when the aqueous solution does not contain halogen elements and a voltage of 20V (1930) is used in the process of manufacturing the filter by electrodeposition.
[0165] Therefore, it can be seen from the second embodiment that, in order not to include halogen elements harmful to the human body, relatively equivalent performance can be achieved by applying a higher voltage to the filter produced by the electrodeposition method.
[0166] The filter manufacturing method described above can manufacture a filter that is simpler and less expensive than conventional processes by using electrodeposition.
[0167] In various embodiments of the present disclosure, the filter is formed based on the anisotropic growth characteristics of copper (having non-uniform growth rate depending on the atomic plane). Therefore, in order to produce a large area filter, it is important to manufacture a filter with non-uniform growth rate on a micro-nano scale and uniform growth rate on a bulk scale (total filter area scale).
[0168] Therefore, hereinafter, a method for improving uniformity of a filter is provided. Hereinafter, the method for improving uniformity of a filter can be applied in the same manner to a filter formed using the above-mentioned first embodiment and a filter formed using the above-mentioned second embodiment.
[0169] First, in the following embodiments, the conditions for improving the uniformity of a large area filter in an electrodeposition process will be described. The conditions for improving the uniformity of a large area filter can be obtained from Figure 20 to Figure 2 2 is obtained. For example, in the present disclosure, by using an electrochemical simulation tool, it is possible to describe the influence of variables such as whether the electrode is open on one side or both sides, the distance between the electrodes on the uniformity of the result during the electrodeposition process. In addition, the manufacturing conditions of the large area filter obtained based on the simulation results will be described. Use the two-dimensional axisymmetric geometry of COSMOL 5.5a software and the tertiary current distribution (TCD ed) model with electrical neutrality to simulate. The variables used are shown in Table 3 below.
[0170] [Table 3]
[0171] Fig. 20 The simulation environment is shown. For simulation, as shown in (a), in a state where the electrolyte 2010 height is 60 mm in a cylindrical electrolytic cell 2000 with a diameter of 140 mm, it is assumed that a copper mesh 2006 and a copper plate 2004 with a diameter of 4 inches are used for electrodeposition. Based on this, the geometry shown in (b) and the mesh shown in (c) are formed. In the geometry shown in (b), the copper plate can be a counter electrode and the copper mesh can be a working electrode. Through simulation, it was confirmed that the number of nodes of the large area filter was 8,890, the minimum unit mass was 0.4428, and the average unit mass was 0.9866.
[0172] Fig.21A , Fig. 21B , Fig. 21C and Fig.21D A simulation graph is shown when the counter electrode participates in an electrochemical reaction.
[0173] Fig.21A shows the time-dependent electrodeposition thickness as a function of the distance from the central axis when both sides of the counter electrode participate in the electrochemical reaction. Fig. 21B The time-based electrodeposition thickness as a function of distance from the central axis is shown when a single face of the counter electrode participates in a site chemical reaction. Fig. 21C The electric field distribution when both sides of the electrode participate in the electrochemical reaction is shown. Fig.21D The electric field distribution when a single surface of the electrode participates in the electrochemical reaction is shown.
[0174] refer to Fig.21A and Fig. 21B With respect to the description of the time-based electrodeposition thickness varying according to distance, it can be understood that the electrodeposition thickness uniformity is higher when only a single side of the electrode participates in the electrochemical reaction than when both sides of the electrode participate in the electrochemical reaction.
[0175] At the same time, reference Fig. 21C and Fig.21D The description of the ion flow shows that when both sides of the counter electrode participate in the electrochemical reaction, the ions supplied from the outer surface are concentrated on the outer side of the working electrode. On the other hand, it can be seen that when only a single side of the counter electrode participates in the electrochemical reaction, the ions are less concentrated on the outer side of the working electrode.
[0176] Fig.22A , Fig. 22B and Fig. 22C A simulation graph showing changes in the distance between electrodes when a single surface of the counter electrode participates in the electrochemical reaction is shown.
[0177] Fig.22A , 22B and 22C show the time-based electrodeposition thickness that varies with the distance from the central axis of the working electrode and the electric field distribution that varies with the distance from the central axis of the working electrode when only a single side of the counter electrode participates in the electrochemical reaction when the distance between the counter electrode and the working electrode is 5 mm, 10 mm, and 20 mm, respectively.
[0178] Reference describes the type of electrodeposition that varies depending on the distance between the counter electrode and the working electrode. Fig.22A , 22B 22C, it can be seen that a flat surface having a constant electrodeposition thickness exists in a portion at a certain distance from the central axis. In addition, it can be seen that the shorter the distance between the counter electrode and the working electrode, the longer the flat surface portion. For example, it can be understood that when the distance between the counter electrode and the working electrode is as Fig.22A When the distance between the counter electrode and the working electrode is as shown, the flat surface portion is the longest. Fig. 22C Shown is maximum (20mm) with flat surface section shortest.
[0179] Through the above Figures 20 to 22C The simulation shown can find that the narrower the distance between the copper plate (i.e., the counter electrode) and the copper mesh (i.e., the working electrode in the electrodeposition process), the higher the uniformity of the formed filter. It can also be found that compared with allowing both sides of the copper plate to participate in the electrochemical reaction, allowing only one side of the copper plate to participate in the electrochemical reaction can further improve the uniformity of the filter.
[0180] Therefore, in an embodiment of the present disclosure, in order to improve the uniformity of the filter, the distance between the copper plate (or metal plate) and the copper mesh (or metal mesh) is set to be as narrow as about 5 mm, and only one side of the copper plate is involved in the electrodeposition process. According to this embodiment, one of the two sides of the copper plate is opened and the other side is closed, so that only one side of the copper plate can participate in the electrochemical reaction. For example, by using a material that cannot cause an electrochemical reaction in the electrolytic cell, one of the two sides of the copper plate can be closed so that it is not exposed to the outside.
[0181] Next, in the following embodiment, a method for improving uniformity of a filter after the filter is formed through an electrodeposition process will be described.
[0182] According to this embodiment, the uniformity of large area filters can be improved by mechanically compressing the filters.
[0183] Fig.23 The concept of mechanically compressing a filter formed by electrodeposition is shown.
[0184] refer to Fig.23 , (a) shows a filter formed by electrodeposition, (b) shows a mechanical compression process of the filter, and (c) shows a filter that has been compressed and deformed.
[0185] Will Fig.23 The filter 2301 formed by electrodeposition shown in (a) is arranged between the first and second silicon pads 2311 and 2312 (as shown in (b)), and at least one roller 2321 is used to compress the filter 2301 between the first and second silicon pads 2311 and 2312, thereby obtaining a compressed and deformed filter 2331, as shown in (c). The roller 2321 can be a heating roller containing a heater. According to this embodiment, the filter 2301 can be mechanically compressed by rolling the heating roller on each of the two sides of the filter 2301.
[0186] Fig.24 The filter is shown before and after compression.
[0187] Fig.24 24 shows a state in which one side 2421 of the filter 2401 formed by electrodeposition is rolled by the heating roller 2403 and the other side 2411 is not compressed by the heating roller 2403. Fig.24 In the figure, enlarged views 2413 and 2423 show a surface of the other side 2411 not rolled by the heating roller 2403 and a surface of the side 2421 rolled by the heating roller 2403, and enlarged views 2415 and 2425 show the side surface of the other side 2411 not rolled by the heating roller 2403 and the side surface of the side 2421 rolled by the heating roller 2403.
[0188] exist Fig.24 In the figure, it can be seen from the enlarged images 2413 and 2423 that the uniformity of the filter after being rolled by the heating roller 2403 is improved compared to the filter before being compressed. Moreover, it can be seen from the enlarged images 2415 and 2425 that the thickness of the filter after being rolled by the heating roller 2403 is less than the thickness before the filter is compressed.
[0189] Fig.25 is a graph showing the filter thickness as a function of the pressure applied during mechanical compression, Fig.26 The filter thickness is shown as a function of the pressure applied during mechanical compression.
[0190] refer to Fig.25 and Fig.26 It can be seen that when pressure is applied by mechanical compression, the thickness of the filter becomes thinner and the uniformity can be improved by reducing the thickness deviation.
[0191] Fig. 27 The pilling test results of the filters are shown.
[0192] Fig. 27 The results of a pilling test on a filter using a glass slide 2703 attached with double-sided tape 2701 are shown.
[0193] refer to Fig. 27 It can be found that the particle dropout rate of the uncompressed filter is 99.803%, the particle dropout rate of the filter compressed at 35 kgf is 11.970%, and the particle dropout rate of the filter compressed at 70 kgf is 11.833%. That is, it can be seen that when the filter is compressed at a higher pressure, the particle dropout rate decreases due to the double-sided tape, thereby obtaining mechanical stability.
[0194] Next, in the following embodiment, a method for improving the pressure drop (or pressure difference) of a filter will be described. The pressure difference refers to the pressure difference between the inlet and outlet of the filter.
[0195] The following embodiments may be used together with at least one of the above embodiments. For example, the following method of improving pressure difference may be applicable to a compressed filter or an uncompressed filter.
[0196] Fig.28 Factors influencing the pressure difference in the filter are shown.
[0197] like Fig.28 As shown, the larger the diameter of the wire, the smaller the area of the filter opening portion, and accordingly, the greater the pressure difference of the filter. Therefore, in the following embodiment, a method of increasing the opening portion diameter 2801 by reducing the wire diameters 2803 and 2813 will be described.
[0198] According to this embodiment, in order to improve the pressure difference of the filter, the diameter of the metal wire can be reduced by using hydrogen during the heat treatment of the filter.
[0199] Fig.29 This is a diagram of the structure of the filter being heat treated using hydrogen.
[0200] like Fig.29 As shown, the compression filter 2911 is disposed on a graphite plate 2913, and the graphite plate 2913 on which the filter 2911 is disposed is disposed in a vacuum tube 2903. In order to heat-treat the filter, a heating element 2921 and a coil 2923 may be disposed around the vacuum tube 2903 to heat the vacuum tube 2903.
[0201] According to this embodiment, when the vacuum tube 2903 is heated, a mixed gas including hydrogen (e.g., H2 / Ar gas) may be injected into the vacuum tube 2903. When the mixed gas is injected into the vacuum tube 2903, an oxide layer (e.g., CuO or Cu2O) formed on the surface of the metal plate (e.g., copper plate) undergoes a reduction reaction with hydrogen (CuO+H2→Cu+H2O). (g) 、Cu2O+H2→2Cu+H2O (g) ) and can be changed into pure copper, so that the diameter of the metal wire in the metal plate can be reduced. The gas existing in the vacuum tube 2903 after the heat treatment can be provided to the air compressor 2905.
[0202] Fig.30 is a graph showing the relationship between the average diameter of the metal wire and the temperature change during the heat treatment of the filter.
[0203] Fig.30 Curve 3010 is shown when the filter is heat treated using conventional argon gas and curve 3020 is shown when the filter is heat treated using hydrogen gas as proposed in the present disclosure.
[0204] refer to Fig.30 It can be understood that when the filter is heat-treated at 400°C, the wire diameter when hydrogen is used is slightly smaller than the wire diameter when argon is used. In addition, it can be understood that when the filter is heat-treated at 500°C, the wire diameter when argon is used increases rapidly, while when the filter is heat-treated at 600°C, there is no difference between the wire diameter when hydrogen is used and the wire diameter when argon is used. This is because the electrodeposition structure is deformed due to the excessively high temperature.
[0205] Fig.31 Filters heat treated using conventional argon and hydrogen gases as proposed in the present disclosure are shown.
[0206] By using conventional argon gas to heat treat the filter such as Fig.31As shown in (a), (b) and (c), the filter using hydrogen for heat treatment proposed in the present disclosure is as follows Fig.31 As shown in (d), (e) and (f).
[0207] refer to Fig.31 It can be seen that at 400°C, the diameter of the wire in the filter heat treated using hydrogen is slightly smaller than the diameter of the wire in the filter heat treated using argon. However, it can be seen that at 500°C, the diameter of the wire in the filter heat treated using hydrogen is 1.1 μm, which is significantly smaller than the 1.8 μm diameter of the wire in the filter heat treated using argon. It can be seen that at 600°C, the electrodeposited structure of the filter is deformed, so the diameter of the wire increases when using hydrogen and argon.
[0208] Fig.32 The pilling test results of the filters are shown.
[0209] Fig.32 The results of a pilling test on a filter using a glass slide 3220 attached with double-sided tape 3210 are shown.
[0210] refer to Fig.32 It can be seen that the particle loss rate of the filter that was not heat-treated and not compressed was 99.803%, and the particle loss rate of the filter that was compressed only at 40 kgf was 11.970%. In addition, it can be seen that the particle loss rate of the filter that was heat-treated only at 500°C was 11.833%, and the particle loss rate of the filter that was compressed at 40 kgf and then heat-treated at 500°C was the lowest at 0.584%. That is, it can be seen that when the compression filter is heat-treated using hydrogen, the mechanical stability can be improved by minimizing the particle loss rate.
[0211] As described above, the filter manufactured by at least one of the plurality of methods can be washed for reuse after being used to filter dust. According to the present embodiment, the pressure difference of the filter can be restored to its original state by washing the used filter with acetone or hydrogen chloride (HCl). This is because dust is very soluble in acetone or hydrogen chloride.
[0212] Fig.33 A used filter and a cleaned filter are shown. A filter manufactured using at least one of the methods proposed in the present disclosure is shown. Fig.33 The filter obtained by filtering fine dust for 40 minutes is as shown in (a). Fig.33 The filter after washing with purified water is shown in (b). The filter after washing with acetone is shown in (d). The filter after washing with hydrogen chloride is shown in (e).
[0213] refer to Fig.33It can be seen that washing the filter with acetone or hydrochloric acid can remove more dust than washing the filter with purified water.
[0214] Fig.34 is a graph showing the change in differential pressure due to cleaning. Fig.34 It can be understood that the pressure difference 3401 of the filter after washing with hydrogen chloride at a flow rate of 2 cm / s, the pressure difference 3403 of the filter after washing with hydrogen chloride at a flow rate of 5 cm / s, and the pressure difference 3405 of the filter after washing with hydrogen chloride at a flow rate of 10 cm / s are all the same as the pressure difference of the corresponding filter before use. That is, it can be seen that by washing the used filter with hydrogen chloride, the pressure difference of the filter is restored to the pressure difference of the initial manufacturing state.
[0215] As described above, according to various embodiments of the present disclosure, a filter can be manufactured by electrodeposition, and the uniformity of the filter can be improved by applying mechanical compression to the formed filter. In addition, the pressure difference of the filter can be improved by performing a hydrogen-based heat treatment on the formed filter and / or the compression filter. Moreover, the pressure difference of the used filter can be restored to the initial pressure difference by washing the used filter with acetone or hydrogen chloride.
[0216] As described above, according to various embodiments of the present disclosure, a nanoporous Cu air filter with antibacterial properties can be manufactured. For example, the filter manufactured according to various embodiments of the present disclosure can capture fine dust physically or by electrostatic action, and can have reusability, antibacterial properties, and high conductivity according to the characteristics of copper.
[0217] Sequence Listing Free Text
[0218] 100: Electrolysis device 110: Electrolysis cell
[0219] 120: Power supply 130: Metal mesh
[0220] 140: Metal plate 150: Aqueous solution
Claims
1. A metal air filter comprising: A filter formed of a metal material by electrodeposition and having a nano-branched structure formed by the conduction of bromide ions contained in an aqueous solution provided in an electrolytic cell for the electrodeposition; an ionizer that imparts a negative charge to particles to be captured by the filter; as well as a power source that provides a positive voltage to impart a positive charge to the filter and provides a negative voltage to the ionizer; wherein the filter is formed by additionally performing a hydrochloric acid washing process to remove bromide ions contained in the filter obtained by electrolysis; and The filter formed by the electrodeposition is additionally subjected to a heat treatment using hydrogen gas to form the filter so as to reduce the diameter of the nano branches.
2. The metal air filter according to claim 1, wherein: The filter is formed by electrodeposition of an electrolyte in an electrolytic cell comprising a metal mesh attached to a cathode, a metal plate attached to an anode, and an aqueous solution.
3. The metal air filter according to claim 2, wherein: The positive voltage is 10V.
4. The metal air filter according to claim 2, wherein: The voltage applied between the cathode and the anode was 0.7V.
5. The metal air filter according to claim 2, wherein: The aqueous solution includes copper sulfate and sulfuric acid, and wherein the voltage applied between the cathode and the anode is 2.4V.
6. The metal air filter according to claim 2, wherein: Only one of the two surfaces of the metal plate in the electrolytic cell is opened so that only the open surface of the two surfaces of the metal plate participates in the electrochemical reaction of the electrodeposition, and wherein the distance between the metal mesh and the metal plate in the electrolytic cell is set to 5 mm.
7. The metal air filter according to claim 1, wherein: The filter formed by the electrodeposition is additionally subjected to a mechanical compression process to obtain the filter.
8. The metal air filter according to claim 1, wherein: The heat treatment using hydrogen is performed by the steps of: placing a graphite plate in a vacuum tube, on which the filter formed by the electrodeposition is placed; injecting a mixed gas containing hydrogen into the vacuum tube; and applying heat to the vacuum tube.
9. A method for manufacturing a metal filter, the method comprising: connecting a metal mesh, in which a metal wire is wound, to the cathode of the electrolytic cell; connecting a metal plate to an anode of the electrolytic cell; adding an aqueous solution including bromide ions so that the metal mesh and the metal plate of the electrolytic cell are immersed; as well as forming the metal filter having a nano-branched structure formed by the guidance of bromide ions by applying a voltage between the cathode and the anode of the electrolytic cell to perform electrolysis; Wherein, forming the filter further comprises: connecting the nano-branches in the filter obtained by the electrolysis to each other and performing heat treatment using hydrogen to reduce the diameter of the nano-branches; and Wherein, forming the filter further comprises: performing a hydrochloric acid cleaning process to remove bromide ions contained in the filter obtained by the electrolysis.
10. The manufacturing method according to claim 9, wherein: The voltage applied between the cathode and the anode was 0.7V.
11. The manufacturing method according to claim 9, wherein: The aqueous solution includes copper sulfate and sulfuric acid, and wherein the voltage applied between the cathode and the anode is 2.4V.
12. The manufacturing method according to claim 9, wherein: Forming the filter further includes: performing a mechanical compression process on the filter obtained by the electrolysis.
13. The manufacturing method according to claim 9, in, Only one of the two sides of the metal plate in the electrolytic cell is opened, and Wherein, the distance between the metal mesh and the metal plate in the electrolytic cell is set to 5 mm.
14. A filter for filtering particles contained in air, the filter being formed of a metal material by electrodeposition and having a nano-branched structure, wherein: forming the nano-branched structure by guiding bromide ions contained in an aqueous solution provided in an electrolytic bath for the electrodeposition; wherein the nano-branches of the filter are connected to each other by a hydrogen-based heat treatment; and The bromide ions used to form the filter are removed through a hydrochloric acid cleaning process.
15. The filter according to claim 14, wherein The filter is formed by the electrodeposition and subsequent mechanical compression.
Citation Information
Patent Citations
Metal plated filter
JP2003164716A
Electrodeposited Nano-Twins Copper Layer and Method of Fabricating the Same
US20130122326A1
Nanoporous metal foam gas filters
US20200086257A1